LANDASAN PENDIDIKAN: KONSEP, TUJUAN, DAN PERANANNYA DALAM SISTEM PENDIDIKAN NASIONAL - Ahmad Gojali Harahap; Laila Damayanti; Umam Khausar Siregar (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The reality shows that educational practices in Indonesia still face a fundamental problem in the form of unclear foundations supporting its implementation, resulting in inconsistency between national education goals and their implementation in the field. This study aims to comprehensively examine the concept of educational foundations, the objectives to be achieved, and their role in the Indonesian national education system. The method used is library research with a descriptive-analytical approach. The results show that educational foundations encompass four main dimensions: philosophical (Pancasila), juridical (Law No. 20/2003 on National Education System), sociological-cultural, and scientific-technological. These four dimensions interact to shape the direction, objectives, and strategies of national education. The conclusion affirms that a deep understanding and consistent implementation of educational foundations is an absolute prerequisite for realizing fully developed Indonesian human beings as mandated by the constitution.